Colobomatous macrophthalmia with microcornea syndrome: report of a new pedigree - TOKER, AYŞE EBRU; ELÇİOĞLU, HURİYE NURSEL; ŞAHİN, ÖZLEM (My University, 2003)
Colobomatous macrophthalmia with microcornea syndrome (MIM 602499) is a very rare eye malformation. To date, only two families with a total number of eight patients have been reported. We report on 13 additional cases in a single three-generation family and describe the eye findings and quantitative parameters of corneal curvature and axial ocular dimensions. All affected relatives had bilateral involvement with typical inferonasal iris coloboma, chorioretinal coloboma, microcornea, and varying degrees of axial enlargement associated with myopia. Additional findings included flatter corneal curvatures and shallower anterior chambers. Iridocorneal angle abnormalities associated with elevation of intraocular pressure were detected in three patients. The pedigree confirms the autosomal dominant pattern of inheritance with complete penetrance.
Keywords: Humans; Turkey; Biometry; Coloboma; Pedigree; Intraocular Pressure; Corneal Diseases; Genes, Dominant; Myopia; Penetrance